2005
DOI: 10.1021/es050194o
|View full text |Cite
|
Sign up to set email alerts
|

PCB Congeners and Dechlorination in Sediments of Lake Hartwell, South Carolina, Determined from Cores Collected in 1987 and 1998

Abstract: Four sediment cores were collected from Lake Hartwell, SC, in 1987 and 1998 and analyzed for polychlorinated biphenyl (PCB) congeners. Total PCBs ranged from -0 to 58 microg/ g. Positive matrix factorization (PMF) was applied to the data sets to determine PCB source profiles. Two factors were determined for each data set. One factor resembled the original estimated PCB mixture of 80% Aroclor 1016 and 20% Aroclor 1254 and the other factor was a dechlorinated version of the mixture. Evidence of a dechlorination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 48 publications
4
59
0
Order By: Relevance
“…For example, SR1-4-SR1-8 have concentrations greater than 50 ppm as do SR4-8-SR4-14. This observation is consistent with a laboratory study by Sokol et al (1998) and a field study of Lake Hartwell sediments (Bzdusek et al, 2005b) that found anaerobic PCB dechlorination occurring at the high PCB concentrations and not at the low PCB concentrations.…”
Section: Pcbs In the Sheboygan River Sedimentssupporting
confidence: 92%
“…For example, SR1-4-SR1-8 have concentrations greater than 50 ppm as do SR4-8-SR4-14. This observation is consistent with a laboratory study by Sokol et al (1998) and a field study of Lake Hartwell sediments (Bzdusek et al, 2005b) that found anaerobic PCB dechlorination occurring at the high PCB concentrations and not at the low PCB concentrations.…”
Section: Pcbs In the Sheboygan River Sedimentssupporting
confidence: 92%
“…Moreover the negative eigenvectors sometimes obtained in PCA are not appropriate when looking for source profiles. While there are numerous examples of pattern analysis using models adapted from multivariate statistics in environmental matrices such as air (Logue et al, 2009;Pekney et al, 2006), soil (Skrbic and Durisic-Mladenovic, 2007) or bottom sediment (Bzdusek et al, 2006a;Bzdusek et al, 2006b;Du et al, 2008), there have been fewer attempts to develop this kind of approach on biota. Examples include an exploration of spatial differences in organochlorine chemical loads in herring gull colonies of the Great Lakes (MacDonald et al, 1992), a study of PCB accumulation features, but neither spatial nor source pattern analysis in the Baltic Sea area (Falandysz et al, 2002), an attempt to differentiate local PCB sources in the Hudson River and its estuary Monosson et al, 2003), and a study of PCB pattern variations across species, trophic levels, and wild versus farmed salmon (Yunker et al, 2011).…”
Section: > Pattern Analysismentioning
confidence: 99%
“…Multivariate receptor models have been used increasingly for the characterization of sources and alteration patterns of chlorinated organic compounds in sediments of complex environmental settings (Jarman, et al, 1997;Johnson, et al, 2000;Barabas, et. al., 2004;Imomoglu, et al, 2002;Magar, et al, 2005;Bzdusek, et al, 2006). A review of these methods, with a focus on PCB forensic application, is provided by Johnson et al, 2007.…”
Section: Step 5: Advanced Chemical Fingerprinting (Acf)mentioning
confidence: 99%
“…In the case of the Henry and Christensen data set, we used their results for UNMIX (the method Henry developed and has used extensively: Henry, et al, 1994;Henry, et al, 2003) and PMF (a method Christensen has published on: Bzdusek, et al, 2006). For PVA, Dr. Glenn Johnson (co-investigator on this research) ran the Henry data set using Matlab code that he wrote and has used in many published studies (Johnson, et al, 2000;Magar, et al, 2005).…”
Section: Data Set 1: Henry and Christensen (2010) Data Setmentioning
confidence: 99%